Membrane fusion proteins are required for oskar mRNA localization in the Drosophila egg chamber. - Ruden, D.M.; Sollars, V.; Wang, X.; Mori, D.; Alterman, M.; Lu, X. (Developmental Biology, 2000)
We used a genetic screen in Drosophila to identify mutations which disrupt the localization of oskar mRNA during oogenesis. Based on the hypothesis that some cytoskeletal components which are required during the mitotic divisions will also be required for oskar mRNA localization during oogenesis, we designed the following genetic screen. We screened for P-element insertions in genes which slow down the blastoderm mitotic divisions. A secondary genetic screen was to generate female germ-line clones of these potential cell division cycle genes and to identify those which cause the mislocalization of oskar mRNA. We identified mutations in ter94 which disrupt the localization of oskar mRNA to the posterior pole of the oocyte. Ter94 is a member of the CDC48p/VCP subfamily of AAA proteins which are involved in homotypic fusion of the endoplasmic reticulum during mitosis. Consistent with the function of the yeast ortholog, ter94-mutant egg chambers are defective in the assembly of the endoplasmic reticulum. We tested whether other membrane biosynthesis genes are required for localizing oskar mRNA during oogenesis. We found that ovaries that are mutant for syntaxin-1a, rop, and synaptotagmin are also defective in oskar mRNA localization during oogenesis. We suggest a pathway for the role of membrane assembly proteins on oskar mRNA localization.